2013
DOI: 10.3109/21691401.2013.848873
|View full text |Cite
|
Sign up to set email alerts
|

Early nerve protection with anterior interosseous nerve in modified end-to-side neurorrhaphy repairs high ulnar nerve injury: a hypothesis of a novel surgical technique

Abstract: High ulnar nerve injuries frequently result in poor functional recovery. The prolonged denervation of target muscle largely accounts for the poor functional outcome. There are no approved effective treatments for high ulnar nerve injuries. However, the technique of reverse end-to-side (RETS) offers novel possibilities. The RETS nerve transfer not only provides earlier motor end-plate reinnervation to "babysit" the target muscle until native axons from the original high nerve regenerate, but also augments the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…The normal structure and function of motor endplates depend on the integrity of nerve fibres and determine the function of skeletal muscles. More importantly, they are considered as the key factors affecting the post-traumatic recovery of neurological function [5,6]. The skeletal muscle function can be evaluated by CMAPs and tetanic contractions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The normal structure and function of motor endplates depend on the integrity of nerve fibres and determine the function of skeletal muscles. More importantly, they are considered as the key factors affecting the post-traumatic recovery of neurological function [5,6]. The skeletal muscle function can be evaluated by CMAPs and tetanic contractions.…”
Section: Discussionmentioning
confidence: 99%
“…As the amplitude size and shape of CMAP depend on the location of recording electrodes [21][22][23][24], the nerve fibre types [18] and the features and number of motor endplate in skeletal muscle [5,25], the measurement of CMAP is not the most direct method in the evaluation of muscle function. However, muscle strength, which is not affected by the electrode Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that axons may grow through an epineural window in a damaged recipient nerve by means, for instance, of a reversed end-to-side neurorraphy. [14,15] Other studies have demonstrated that operative injury to the donor nerve during ESN is the main prerequisite for motor reinnervation of the recipient nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, though motor function of the hand is more important than sensory function for quality of life, motor recovery is less reliable due to progressive motor endplate loss and muscular atrophy, 6 even despite early and well-performed microsurgical nerve repair. 6,7 Current ulnar nerve repair strategies include primary microsurgical repair, conduit-assisted repair, or reconstruction with an autograft or allograft. If the injury occurs around the level of the elbow, then transposition should be considered to minimize tension on the repair.…”
Section: Introductionmentioning
confidence: 99%